Literature, modernism, and dance - Jones, Susan, 1952- (Oxford : Oxford University Press, 2013)
This book explores the complex relationship between literature and dance in the era of modernism. During this period an unprecedented dialogue between the two art forms took place, based on a common aesthetics initiated by contemporary discussions of the body and gender, language, formal experimentation, primitivism, anthropology, and modern technologies such as photography, film, and mechanisation. The book traces the origins of this relationship to the philosophical antecedents of modernism in the nineteenth century and examines experimentation in both art forms. The book investigates dance's impact on the modernists' critique of language and shows the importance to writers of choreographic innovations by dancers of the fin de siecle, of the Ballets Russes, and of European and American experimentalists in non-balletic forms of modern dance. A reciprocal relationship occurs with choreographic use of literary text. Dance and literature meet at this time at the site of formal experiments in narrative, drama, and poetics, and their relationship contributes to common aesthetic modes such as symbolism, primitivism, expressionism, and constructivism. Focussing on the first half of the twentieth century, the book locates these transactions in a transatlantic field, giving weight to both European and American contexts and illustrating the importance of dance as a conduit of modernist preoccupations in Europe and the US through patterns of influence and exchange. Chapters explore the close interrelationships of writers and choreographers of this period including Mallarme, Nietzsche, Yeats, Conrad, Woolf, Lawrence, Pound, Eliot, and Beckett, Fuller, Duncan, Fokine, Nijinsky, Massine, Nijinska, Balanchine, Tudor, Laban, Wigman, Graham, and Humphrey, and recover radical experiments by neglected writers and choreographers from David Garnett and Esther Forbes to Andree Howard and Oskar Schlemmer. -- Cover.
Includes bibliographical references (pages 310-333) and index.
Keywords: Literature and dance; Modernism (Literature)